2011
DOI: 10.1097/wad.0b013e3181f5b8d8
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a New ADAS-cog Composite Using Tree-based Multivariate Analysis

Abstract: Model-based statistical approaches were used to compare the ability of the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog), cerebrospinal fluid (CSF), fluorodeoxyglucose positron emission tomography and volumetric magnetic resonance imaging (MRI) markers to predict 12-month progression from mild cognitive impairment (MCI) to Alzheimer disease (AD). Using the Alzheimer's Disease Neuroimaging Initiative (ADNI) data set, properties of the 11-item ADAS-cog (ADAS.11), the 13-item ADAS-cog (ADAS.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…It also incorporates principle component methodology to account for item correlation. Related methodologies to produce composite scores have been successfully applied including the ADAS Tree (32) and ADAS-cog revisited (33). …”
Section: Discussionmentioning
confidence: 99%
“…It also incorporates principle component methodology to account for item correlation. Related methodologies to produce composite scores have been successfully applied including the ADAS Tree (32) and ADAS-cog revisited (33). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, we observed that CDR-sum score increased at a steeper rate compared to the index. Thus, to overcome this limitation, it has been proposed to create richer cognitive distributions by constructing novel composite scores employing machine learning algorithms, that are able to predict conversion from MCI to AD better than standard cognitive scores (Llano et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Llano et al [96] developed a cognitive test based on ADAS-cog as an alternative to imaging or CSF biomarkers for use as an outcome measure or for subject enrichment in clinical trials. The ADAS.Tree composite was derived by weighting test components of ADAS-cog based on their ability to discriminate between control, MCI, and AD subjects of the ADNI cohort using a Random Forests tree-based algorithm.…”
Section: Methods Papersmentioning
confidence: 99%
“…Llano et al [96] compared the ADAS-cog and MMSE tests with a new form of ADAS-cog in which the subscores were given weights using a Random Forests tree algorithm, thereby resulting in a new metric, the composite ADAS.Tree. Therefore, ADAS.Tree represents a multivariate model in which subscales have been weighted according to their importance in discriminating between AD and control subjects.…”
Section: Studies Of the Adni Cohortmentioning
confidence: 99%
See 1 more Smart Citation